Effect of a community-based pedestrian injury prevention program on driver yielding behavior at marked crosswalks. (August 2016) - Sandt, Laura S.; Marshall, Stephen W.; Rodriguez, Daniel A.; Evenson, Kelly R.; Ennett, Susan T.; Robinson, Whitney R.
Highlights: Estimated effects of enforcement and engineering on driver yielding to pedestrians in crosswalks. Used a pre-post design with control group and examined real and staged pedestrian crossings. Driver yielding rates improved between 4 and 7% at treated locations. Highest yielding rates occurred at high visibility, two-lane, and/or low-speed crossings. Abstract: Background: Few studies have comprehensively evaluated the effectiveness of multi-faceted interventions intended to improve pedestrian safety. "Watch for Me NC" is a multi-faceted, community-based pedestrian safety program that includes widespread media and public engagement in combination with enhanced law enforcement activities (i.e., police outreach and targeted pedestrian safety operations conducted at marked crosswalks) and low-cost engineering improvements at selected crossings. The purpose of this study was to estimate the effect of the law enforcement and engineering improvement components of the program on motor vehicle driver behavior, specifically in terms of increased driver yielding to pedestrians in marked crosswalks. Methods: The study used a pre-post design with a control group, comparing crossing locations receiving enforcement and low-cost engineering treatments (enhanced locations) with locations that did not (standard locations) to examine changes in driver yielding over a 6-month period from 2013 to 2014. A total of 24, 941 drivers were observed in 11, 817 attempted crossing events at 16 crosswalks in five municipalities that were participating in the program. Observations of real pedestrians attempting to use the crosswalks ("naturalistic" crossing) were supplemented by observations of trained research staff attempting the same crossings following an established protocol ("staged" crossings). Generalized estimating equations (GEE) were used to model driver yielding rates, accounting for repeated observations at the crossing locations and controlling other factors that affect driver behavior in yielding to pedestrians in marked crosswalks. Results: At crossings that did not receive enhancements (targeted police operations or low-cost engineering improvements), driver yielding rates did not change from before to after the Watch for Me NC program. However, yielding rates improved significantly (between 4 and 7 percentage points on average) at the enhanced locations. This was true for both naturalistic and staged crossings. Conclusions: This study provides evidence that enhanced enforcement and low-cost engineering improvements, as a part of a broader program involving community-based outreach, can increase driver yielding to pedestrians in marked crosswalks. These data are important for the staff and decision-makers involved in pedestrian safety programs to gain a better understanding of the different engineering and behavioral mechanisms that could be used to improve driver yielding rates.